2021
DOI: 10.1007/s00784-021-03895-8
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss in complying and non-complying periodontitis patients with different periodontal risk levels during supportive periodontal care

Abstract: Objectives To evaluate yearly tooth loss rate (TLR) in periodontitis patients with different periodontal risk levels who had complied or not complied with supportive periodontal care (SPC). Materials and methods Data from 168 periodontitis patients enrolled in a SPC program based on a 3-month suggested recall interval for at least 3.5 years were analyzed. For patients with a mean recall interval within 2–4 months (“compliers”) or > 4 months (“non-compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
0
10
0
5
Order By: Relevance
“…The final goal of periodontal therapy is the retention of teeth during the lifecourse (Eickholz et al, 2008). Different longitudinal studies in periodontal patients have demonstrated that TL can be prevented or significantly reduced in the presence of proper APT (Axelsson et al, 2004;Eickholz et al, 2008;Dannewitz et al, 2016, Farina et al, 2021 and followed by a good SPC programme (Costa et al, 2012;Armitage & Xenoudi, 2016;Costa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final goal of periodontal therapy is the retention of teeth during the lifecourse (Eickholz et al, 2008). Different longitudinal studies in periodontal patients have demonstrated that TL can be prevented or significantly reduced in the presence of proper APT (Axelsson et al, 2004;Eickholz et al, 2008;Dannewitz et al, 2016, Farina et al, 2021 and followed by a good SPC programme (Costa et al, 2012;Armitage & Xenoudi, 2016;Costa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Tooth loss (TL), the most tangible result from periodontitis progression, has physiological and psychological impacts on a patient's life (Costa et al, 2014;Dannewitz et al, 2016;Costa et al, 2019). The effectiveness of periodontal therapy in reducing TL and the importance of patient compliance during supportive periodontal care (SPC) have been previously demonstrated (Axelsson et al, 2004;Faggion Jr et al, 2007;Costa et al, 2012;Costa et al, 2014;Graetz et al, 2015;Armitage & Xenoudi, 2016;Farina et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…23 Tooth loss rate for patient with high periodontitis risk is significantly higher than low-risk patients. 24 In this case, the patient is under the high-risk category due to ACC and smoking habits. 23,25 It is important to start tobacco cessation programmes for the patient to achieve a better outcome of the periodontal disease and reduce the risk of tooth loss during the maintenance period.…”
Section: Discussionmentioning
confidence: 99%
“…At 1-year visit, patients received personalized indications regarding their supportive periodontal therapy (SPT) program based on their periodontal risk level [33][34][35], and were left free to perform SPT at the center where they underwent surgery or other dental settings. At 3 years, patients were recalled for a follow-up visit where clinical and radiographic assessments were performed to evaluate the conditions of peri-implant tissues.…”
Section: Clinical Proceduresmentioning
confidence: 99%